Peran geostrategi dan geopolitik dalam memperkuat ketahanan nasional indonesia - billa, sri alya yunisa; Billa, Sri Alya Yunisa (Maliki Interdisciplinary Journal, 2026)
Indonesia, as the world’s largest archipelagic nation, occupies a strategic geographic position while remaining vulnerable to various threats, both internal and external. This study to analyze the role of geostrategy and geopolitics in strengthening Indonesia’s national resilience. Geostrategy and geopolitics play a crucial role in optimizing the utilization of Indonesia’s geographic potential, natural resources, and strategic location within global dynamics. Its implementation is not limited to the defense and military dimensions, but also includes stengthening maritime connectivity, increasing economic competitiveness, strengthening ideology, and developing socio-cultural cohesion. Furthermore, globalgeopolitical dynamics demand indonesia’s adaptation through integrated and sustainable policies to anticipate multidimensioanl threats, such as regional conflict, disinformation, and economics interdependence. Overall, a comprehensive synergy between geostrategy and geopolitics has the potential to enhance Indonesia’s national resilience, while strengthening of the global strategic environment.